VIITORIO POSSENTI, Approssimazioni all'essere. Scritti di metafisica e morale. Il Poligrafo. Padova 1995. 224 páginas. ISBN 88-7115-062-7. - Massini Correas, Carlos I. (1996)
Fil: Massini Correas, Carlos I. Universidad de Mendoza; Argentina